Penggunaan Akun Media Sosial Instagram: Pengaruhnya terhadap Aktualisasi Kerja Pegawai - Sindy Pramudita; Achmad Nashrudin Priatna; Noerma Kurnia Fajarwati; April Laksana; Meiby Zulfikar (Pusat Riset dan Inovasi Nasional, 2026)
Social media has evolved into more than just a means of communication; It now plays an important role in shaping the image of the institution, providing recognition, and increasing employee motivation and involvement, especially in public service institutions. This study aims to determine the effect of the use of Instagram @dinkopukmperindagkotaserang accounts on employee self-actualization at UPT Pasar Kota Serang. The method used is a descriptive quantitative approach with survey techniques. The population and sample in this study amounted to 40 employees, which were taken using the total sampling technique. Data analysis was carried out with the help of SPSS software version 26, including validity tests, reliability tests, descriptive statistics, and simple linear regression. The results of the study show that the use of Instagram accounts has a significant influence on employee self-actualization. The determination coefficient value of 0.471 shows that 47.1% of the self-actualization variable is influenced by the use of Instagram accounts. These findings indicate that the better the content management and the higher the employee's involvement with the account, the higher the level of self-actualization achieved in carrying out their role as public servants. This study recommends optimizing institutional social media strategies as part of efforts to improve the quality of human resources and the effectiveness of public services.